THE INFLUENCE OF LIFESTYLE, BRAND IMAGE, AND BRAND EQUITY ON EIGER PURCHASING DECISIONS (CASE STUDY ON EIGER CONSUMERS IN MADIUN) - Kurniawati , Varisa; Setyawan , Fery; Wardani , Diana Pramudya (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: The decision-making process of consumers is influenced by various factors, including lifestyle, brand image, and brand equity. Specific Background: For Eiger, a well-known outdoor equipment brand, understanding these influences is crucial, particularly in the context of its consumer base in Madiun. Knowledge Gap: Despite the significance of these factors, limited research has been conducted on their specific impacts on purchasing decisions in the Eiger brand context, especially in Madiun. Aims: This study aims to analyze the influence of lifestyle, brand image, and brand equity on the purchasing decisions of Eiger consumers in Madiun, employing a quantitative approach. Results: The study reveals that lifestyle has a negative and significant impact on purchasing decisions, brand image does not significantly affect purchasing decisions, and brand equity has a positive and significant influence on purchasing decisions. Novelty: These findings provide new insights into the varying impacts of these factors within the Eiger brand, particularly the unexpected negative influence of lifestyle on purchasing decisions, which contrasts with conventional expectations. Implications: The results suggest that Eiger should re-evaluate its marketing strategies in Madiun, particularly by focusing on enhancing brand equity while reconsidering how lifestyle factors are addressed in their promotional efforts. This research contributes to a deeper understanding of consumer behavior in niche markets and offers practical implications for brand management and marketing strategy formulation.